Effect of Frustration on Brain Activation Pattern in Subjects with Different Temperament - Bierzynska, Maria; Bielecki, Maksymilian; Marchewka, Artur; Debowska, Weronika; Duszyk, Anna; Zajkowski, Wojciech; Falkiewicz, Marcel; Nowicka, Anna; Strelau, Jan; Kossut, Malgorzata (Frontiers in Psychology, 2016)
In spite of the prevalence of frustration in everyday life, very few neuroimaging studies were focused on this emotional state. In the current study we aimed to examine effects of frustration on brain activity while performing a well-learned task in participants with low and high tolerance for arousal. Prior to the functional magnetic resonance imaging (fMRI) session, the subjects underwent two weeks of Braille reading training. Frustration induction was obtained by using a novel highly difficult tactile task based on discrimination of Braille-like raised dots patterns and negative feedback. Effectiveness of this procedure has been confirmed in a pilot study using galvanic skin response (GSR) and questionnaires. Brain activation pattern during tactile discrimination task before and after frustration were compared directly. Results revealed changes in brain activity in structures mostly reported in acute stress studies: striatum, cingulate cortex, insula, middle frontal gyrus and precuneus and in structures engaged in tactile Braille discrimination: SI and SII. Temperament type affected activation pattern. Subjects with low tolerance for arousal showed higher activation in the posterior cingulate gyrus, precuneus and inferior parietal lobule (IPL) than high reactivity group. Even though performance in the discrimination trials following frustration was unaltered, we observed increased activity of primary and secondary somatosensory cortex processing the tactile information. We interpret this effect as an indicator of additional involvement required to counteract the effects of frustration.